Performance analysis of zinc cobaltite (ZnCO2O4) as a hole transport layer (HTL) for perovskite solar cell using OghmaNano software and Taguchi method optimization. - M. Rummaja, Mohd Iskandar Dzulkarnain; Idris, Muhammad Idzdihar; M. Napiah, Z. A. F.; Baharudin Zamani, Zarina; Ramlee, Radi Husin; Rashid, M. (2024)
Perovskite solar cells (PSCs) are cost-effective and efficient photovoltaic cells that show great potential as an alternative to silicon solar cells. They possess desirable properties such as high mobility, direct bandgap, long carrier lifetime, and strong light absorption. However, the traditional materials used for the holes transport layer (HTL) in PSCs, such as PEDOT:PSS, SPIRO-OMETAD, and copper(I) iodide, have durability issues and lower carrier mobility. To overcome these challenges, Zinc Cobaltite (ZnCO2O4) with its advantages of hole transport, wide optical bandgap, and solution processability was investigated as a potential alternative HTL material. Through simulations using OghmaNano software and the Taguchi method, the device structure FTO/TiO2/CsPbI3/ZnCO2O4/Au was analyzed, and the performance was optimized by varying the thickness of the ZnCO2O4 layer. The simulation results showed a power conversion efficiency (PCE) of 32.23% with a ZnCO2O4 thickness of 300nm. ANOVA analysis revealed that the ZnCO2O4 thickness as the HTL had the most significant influence on PCE, followed by environmental temperature and the bandgap of ZnCO2O4. In particular, the ZnCO2O4 thickness had a substantial 70% impact on PCE, indicating that adjusting the thickness of ZnCO2O4 could lead to corresponding improvements in PCE.